2017
DOI: 10.1111/nmo.13262
|View full text |Cite
|
Sign up to set email alerts
|

Jackhammer esophagus: Assessing the balance between prepeak and postpeak contractile integral

Abstract: Abnormalities in contractile integral of the postpeak phase are more significant in JH with higher dysphagia scores Although the total postpeak contractile integral was higher in symptomatic patients, this was associated with longer duration of postpeak activity suggesting that dysphagia patients with JH have a defect in the postpeak phase of peristalsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
3
27
0
2
Order By: Relevance
“…The clinical characteristics of JE patients have been poorly reported. Some retrospective cohorts have been reported so far, 2–11 but the number of patients was limited; the most important only included 81 patients 9 . Dysphagia is the most frequent symptom, occurring between 53% and 86% of the patients, associated or not with chest pain or reflux symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics of JE patients have been poorly reported. Some retrospective cohorts have been reported so far, 2–11 but the number of patients was limited; the most important only included 81 patients 9 . Dysphagia is the most frequent symptom, occurring between 53% and 86% of the patients, associated or not with chest pain or reflux symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The negative outcome of this study can be interpreted in two ways. The authors concluded that the study was negative because hypercontractile esophageal motility disorders have a benign natural disease course, with spontaneous improvement after three months in line with some but not all previous reports . Another interpretation could be that patients with hypercontractile esophageal motility disorders have functional esophageal symptoms that are not related to the esophageal hypercontractility, and therefore, these symptoms are not responding to treatment of the hypercontractility.…”
mentioning
confidence: 55%
“…The authors concluded that the study was negative because hypercontractile esophageal motility disorders have a benign natural disease course, with spontaneous improvement after three months in line with some but not all previous reports. [3][4][5][6] Another interpretation could be that patients While pooled together in this study, type III achalasia is probably different from jackhammer and DES, as the relationship between symptoms and abnormal motility seems clearer in type III achalasia and more data on natural history and development to other types of achalasia is available. For DES and jackhammer, a substantial subset of these patients may have functional symptoms that therefore do not respond to reduction of hypercontractility with botulinum toxin.…”
mentioning
confidence: 90%
“…20 When esophageal contractions in patients with HE are divided into a pre-peak and a post-peak phase, regardless of the presence or absence of multiple peaks, postpeak hypercontractility is associated with higher overall contraction vigor and higher dysphagia scores. 21,22 Based on these observations, it seems wise to take esophageal pressure wave morphology into account in future studies on HE, to avoid lumping of repetitive and non-repetitive HE subtypes and not to use "jackhammer esophagus" as a pars pro toto term.…”
Section: Key Pointsmentioning
confidence: 99%
“…Recent observations suggest, however that, whereas the onset of the pressure waves may be peristaltic, subsequent peaks often propagate in a chaotic fashion, and that an increased "chaotic ratio" is associated with higher dysphagia symptom scores. 21,22 To accept a cause-effect relationship, a correlation between contractile vigor and presence or severity of dysphagia would help. For this reason, various studies have attempted to link higher contraction vigor to more frequent or more severe symptoms (both dysphagia and chest pain).…”
Section: A Ssociation With Symp Tomsmentioning
confidence: 99%